Pengaruh Struktur Modal, Likuiditas, dan Modal Intelektual terhadap Nilai Perusahaan Makanan dan Minuman di BEI 2022-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the impact of capital structure, liquidity, and intellectual capital on firm value within Indonesia's food and beverage sector. Focusing on companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2023, the research employs Tobin's Q as the measure of firm value, while utilizing Debt to Equity Ratio (DER), Current Ratio (CR), and Value Added Intellectual Coefficient (VAIC) to assess capital structure, liquidity, and intellectual capital respectively. Using a quantitative methodology, the analysis applies panel data regression techniques to a purposively selected sample of 30 companies. The study reveals that capital structure demonstrates a significant negative relationship with firm value, suggesting that higher debt levels may diminish company valuation due to increased financial risks and unfavorable market perceptions. Similarly, liquidity shows a negative correlation, indicating that excessive liquid assets may be interpreted as poor resource allocation by investors. Interestingly, the findings show that intellectual capital does not exert a statistically significant influence on firm value in this sector. This suggests that investors in Indonesia's food and beverage industry may prioritize tangible financial metrics over intangible assets when evaluating companies. When considered collectively, these three factors account for 95.8% of the variation in firm value, with the remaining variance attributable to other unexamined factors. These results have important implications for corporate financial management and investment decision-making. The study recommends that companies maintain balanced debt levels and optimize their liquidity management to enhance shareholder value. While intellectual capital may not currently impact valuations significantly, its strategic development remains crucial for long-term competitiveness. The findings contribute to academic literature on corporate finance while offering practical guidance for investors and corporate managers in emerging markets.